ANALISIS ANGGARAN RITUAL ADAT SAPU BERBASIS MOBILE WEB - Bata, Emanuel Safirman (STIKOM Uyelindo Kupang, 2019)
The Sapu ceremony is a ceremony carried out by the people of So'a in general and the people of Lo'a in particular. This ceremony is held only for adult men both those who are married and those who have not. To be able to carry out a successful event requires careful planning and good implementation. The choice of place of ceremony, invitation, consumption and luggage must be planned from the start. Some of the reasons for the swelling rituals of traditional Sapu rituals are that the organizers of the rituals focus less on the amount of the budget, follow all the wishes of others, lack information, handle everything themselves and are less strict in determining the number of guests. Traditional Sapu rituals, like other projects, require careful planning in which the amount of the budget is followed by the deadline that must be met. Planning traditional Sapu rituals is a complex job, and can be large and spend a considerable amount of time. If it is not well planned, the traditional Sapu ritual cannot run smoothly. Based on these problems, a mobile-based website was built that can help the admin, calculating the amount of budget needed to hold the traditional Sapu ritual. Facilitate the process of recapitulation and printing of financial reports per participant and total funds overall. In terms of appearance, it is good, interactive and user friendly, easy to read and understand, and the choice of colors that are comfortable and beautiful to look at. The website is created using the PHP programming language. To manage the database management system (DBMS), MySQL is used.